Neuroimaging in dementia - Barkhof, Frederik 1962-.; SpringerLink (Online service). (Berlin London Springer, 2011)
Against a background of an ever-increasing number of patients, new management options, and novel imaging modalities, neuroimaging is playing an increasingly important role in the diagnosis of dementia.  This up-to-date, superbly illustrated book aims to provide a practical guide to the effective use of neuroimaging in the patient with cognitive decline. It sets out the key clinical and imaging features of the wide range of causes of dementia and directs the reader from clinical presentation to neuroimaging and on to an accurate diagnosis whenever possible.  After an introductory chapter on the clinical background, the available "toolbox" of structural and functional neuroimaging techniques is reviewed in detail, including CT, MRI and advanced MR techniques, SPECT and PET, and image analysis methods. The imaging findings in normal ageing are then discussed, followed by a series of chapters that carefully present and analyze the key imaging findings in patients with dementias. A structured path of analysis follows the main presenting feature: disorders associated with primary gray matter loss, with white matter changes, with brain swelling, etc. Throughout, a practical approach is adopted, geared specifically to the needs of clinicians (neurologists, radiologists, psychiatrists, geriatricians) working in the field of dementia, for whom this book should prove an invaluable resource.
Clinical background: Definition of dementia. Prevalence and incidence. Nosological approach. Differential diagnosis. Multi-disciplinary integration -- The toolbox: Structural imaging. Feature extraction. Advanced MR techniques. SPECT and PET -- Normal Ageing: Brain volume loss. Enlarged perivascular (Virchow-Robin) spaces and lacunes. Age-related white matter changes. Iron accumulation. Hidden age-related changes in brain tissue -- Primary gray matter loss: Alzheimer?s disease. Frontotemporal lobar degeneration. Dementia with Parkinsonism. Dementia in other movement disorders. Prion-linked dementias. Recreational drugs and alcohol -- Vascular Disease: history and nosology. Large vessel vascular dementia. Small vessel vascular dementia. Vasculitis. Systemic hypoxia. Mixed dementia and interrelationship VaD/AD -- Disorders mainly affecting white matter: Infections. Inflammatory disorders. Inborn errors of metabolism. Toxic leukencephalopathy and dementia. Post-therapy effect. Trauma -- Dementias with associated brain swelling. Giant VRS. Infections. Neoplastic disease and radiation necrosis. Auto-immune limbic encephalitis. Normal pressure hydrocephalus (NPH). Arteriovenous malformation (AVM) and fistula (AVF). Reversible posterior leukencephalopathy (RPLS). Anti-amyloid therapy.
Electronic reproduction.
Keywords: Brain -- Imaging; Dementia -- Diagnosis; Electronic books